The molecular mechanisms of quality difference for Alpine Qingming green tea and Guyu green tea by integrating multi-omics - Xiao, Hongshi; Yong, Jie; Xie, Yijie; Zhou, Haiyan (Frontiers in Nutrition, 2023)
Harvest time represents one of the crucial factors concerning the quality of alpine green tea. At present, the mechanisms of the tea quality changing with harvest time have been unrevealed. In the current study, fresh tea leaves (qmlc and gylc) and processed leaves (qmgc and gygc) picked during Qingming Festival and Guyu Festival were analyzed by means of sensory evaluation, metabolomics, transcriptomic analysis, and high-throughput sequencing, as well as their endophytic bacteria (qm16s and gy16s). The results indicated qmgc possessed higher sensory quality than gygc which reflected from higher relative contents of amino acids, and soluble sugars but lower relative contents of catechins, theaflavins, and flavonols. These differential metabolites created features of light green color, prominent freshness, sweet aftertaste, and mild bitterness for qmgc. Flavone and flavonol biosynthesis and phenylalanine metabolism were uncovered as the key pathways to differentiate the quality of qmgc and gygc. Endophytic bacteria in leaves further influence the quality by regulating the growth of tea trees and enhancing their disease resistance. Our findings threw some new clues on the tea leaves picking to pursue the balance when facing the conflicts of product quality and economic benefits.